Hospital-Acquired Methicillin-Resistant Staphylococcus aureus: Epidemiology, Treatment and Control - Coleman Rotstein (Canadian Journal of Infectious Diseases and Medical Microbiology)
Antimicrobial-resistant organisms are an expanding problem, resulting in increased morbidity and mortality, prolonged hospital stay, and heightened health care costs for care and antimicrobial management. Methicillin-resistant Staphylococcus aureus (MRSA) has emerged as a major hospital-acquired, antimicrobial-resistant pathogen. MRSA not only colonizes hospitalized patients but has a propensity to produce more serious, life- threatening infection than methicillin-susceptible strains. Numerous risk factors, including antimicrobial use and proximity to a patient harbouring MRSA, have been linked to the acquisition of MRSA. Although vancomycin has been the mainstay of therapy for MRSA, failures have been reported due to reduced susceptibility to this agent. Other available therapeutic agents for MRSA include trimethoprim-sulfamethoxazole, tetracycline, fusidic acid, rifampin (in combination with other effective agents) and linezolid. Potential therapeutic agents that are currently under investigation include daptomycin, dalbavancin, tigecycline, ceftobiprole and iclaprim. Only enhanced infection control practices can halt the progressive transmission of MRSA in the hospital environment. However, such measures have not quite fulfilled their promise in clinical studies. Moreover, eradication of MRSA colonization is controversial and may promote greater resistance. A multidisciplinary approach to the prevention, containment and treatment of MRSA is necessary.